Ceramic water permeable brick with imitated stone texture and manufacturing method of ceramic water permeable brick
By adopting multi-layer structure design and advanced spray glazing and digital inkjet technology in the manufacturing process of ceramic permeable bricks, the problem of single color and texture of existing ceramic permeable bricks is solved, and the presentation of multiple textures and colors is achieved. And improve the anti-fouling and anti-slip performance of the product.
Patent Information
- Application Number
- CN202411385751.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The color and texture of existing ceramic permeable bricks are relatively single, and they cannot perfectly present the marble texture. At the same time, they require high product purity and complex process.
In the manufacturing process of ceramic permeable bricks, a multi-layer structure design is adopted, including a base material layer, a fabric layer, a base glaze decorative layer, a pattern decorative layer, a top glaze decorative layer and a functional glaze decorative layer, combined with spray glazing and digital inkjet technology to achieve the presentation of a variety of textures and colors.
It achieves the reproduction of various textures and colors of ceramic permeable bricks. The product texture is clear, the anti-fouling performance and anti-slip performance are significantly improved, and the process is relatively simple and easy to implement.
Smart Images

Figure CN119306472A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of building materials, and in particular to a ceramic water-permeable brick with imitation stone texture and a manufacturing method thereof. Background technology:
[0002] Ceramic permeable bricks are a kind of ceramic bricks that can be reused environmentally to improve the urban heat island effect and reduce the pressure of urban drainage. In response to the call of "sponge city", they have entered the market's choice field. At present, most of the ceramic permeable brick products on the market are unglazed and secondary fabric products. First: the fabric layer uses waste ceramic particles and adds colorants to achieve the color required by customers. Second: inkjet on the basis of the fabric layer. The colors shown by the two decoration methods are relatively single.
[0003] At present, there are studies on ceramic permeable bricks in the industry. Patents such as CN117229082A, CN116675554A, and CN113003989A disclose the traditional process of using ceramic waste as the main material, supplemented by other solid waste, and adding binders and colorants for stirring and firing. These process characteristics are that the color is developed by adding inorganic colorants, and the whole brick can only present one color, which is relatively single.
[0004] The key points of the imitation marble disclosed in CN109534786A are: based on the traditional permeable brick, the protective glaze and inkjet process are added. 1) This process adjusts the grayscale to 60%-70%, and the texture presented is blurred, and the marble texture cannot be perfectly presented; 2) This process has high requirements on the purity of the product body. It is urgent to solve the above problems and develop new permeable ceramic tiles. Summary of the invention:
[0005] The present invention solves the problems existing in the prior art and provides a ceramic permeable brick with imitation stone texture and a manufacturing method thereof. The ceramic permeable brick obtained by the manufacturing method proposed by the present invention has the effect of imitating stone. The product has stone textures such as sesame white, sesame gray, sesame black, night snow, and langtaosha. At the same time, the process is simple and easy to implement.
[0006] The purpose of the present invention is to provide a ceramic permeable brick with imitation stone texture, which comprises, from bottom to top, a body base material layer, a body surface layer, a base glaze decorative layer, a pattern decorative layer, a surface glaze decorative layer and a functional glaze decorative layer. According to GB / T25993-2023 permeable pavement brick and permeable road slab standard, the ratio of nominal length to nominal thickness is less than or equal to 4 for permeable pavement bricks, the splitting tensile strength is ≥3.0 MPa, and the water permeability coefficient is greater than or equal to 1.0×10 -2 cm / s; when the ratio of nominal length to nominal thickness is greater than 4, it is a permeable road slab, the flexural strength is ≥3.0 MPa, and the permeability coefficient is greater than or equal to 1.0×10 -2cm / s.
[0007] The ceramic permeable brick has a base material layer thickness of 22-75 mm, a surface material layer thickness of 8-10 mm, a base glaze decorative layer thickness of 0.1-0.2 mm, a surface glaze decorative layer thickness of 0.05-0.1 mm, and a functional glaze decorative layer thickness of 0.5-1 mm.
[0008] Preferably, the surface glaze decoration layer is prepared by the following steps: spray glazing is performed on the pattern decoration layer to obtain the surface glaze decoration layer, and the process parameters of the spray glazing are: the specific gravity of the glaze slurry is 1.15-1.25g / cm 3 , glaze slurry flow rate 11 ~ 13s / 100mL, glaze slurry sieve residue 250 mesh sieve residue 0.5% ~ 0.7%, glaze amount 145 ~ 220g / m 2 .
[0009] Preferably, the glaze formula in the glaze decorative layer is: calculated by dry weight, including 28-32 parts of potassium feldspar, 0.1-0.3 parts of methyl cellulose, 0.1-0.3 parts of sodium tripolyphosphate, 15-20 parts of barium carbonate, 8-10 parts of dolomite, 13-18 parts of sodium feldspar, 6-10 parts of calcined talc, 3-5 parts of zinc oxide, 5-10 parts of kaolin and 5-10 parts of low-temperature frit, and an additional 45-55 parts of water.
[0010] Further preferably, the glaze formula in the glaze decorative layer is: calculated by dry weight, including 30 parts of potassium feldspar, 0.2 parts of methyl cellulose, 0.2 parts of sodium tripolyphosphate, 18 parts of barium carbonate, 9 parts of dolomite, 15 parts of sodium feldspar, 8 parts of calcined talc, 4 parts of zinc oxide, 8 parts of kaolin and 8 parts of low-temperature frit, and an additional 50 parts of water.
[0011] Preferably, the functional glaze formula in the functional glaze decorative layer is: calculated by weight, including 62-67 parts of dry particle suspension agent, 0.1-0.3 parts of methyl cellulose, 13-20 parts of water and 15-18 parts of environmentally friendly dry particles.
[0012] Further preferably, the functional glaze formula in the functional glaze decorative layer is: calculated by weight, including 66 parts of dry particle suspension agent, 0.1 parts of methyl cellulose, 16 parts of water and 18 parts of environmentally friendly dry particles.
[0013] The present invention also provides a method for manufacturing the ceramic permeable brick with imitation stone texture, comprising the following steps:
[0014] (1) Crush the waste ceramic bricks to obtain crushed materials, remove iron from the crushed materials and classify them according to their particle sizes, namely: 6-8 mesh, 8-14 mesh, 14-30 mesh and below 30 mesh;
[0015] (2) The crushed ceramic waste brick particles classified in step (1) are respectively prepared into a surface material and a base material according to whiteness and particle size, the base material is mixed with a binder, the moisture content of the mixed ingredients is controlled at 3.8% to 4.2%, and the base material blank is obtained after being evenly mixed, and the base material blank is pressed into a blank base material layer;
[0016] (3) mixing the fabric obtained in step (2) with a binder, controlling the moisture content of the mixed ingredients to be 3.8% to 4.2%, mixing evenly to obtain a fabric blank, and pressing the fabric blank into a blank fabric layer;
[0017] (4) Applying a base glaze on the surface layer of the blank to obtain a base glaze decorative layer. The process parameters for applying the base glaze are: glaze slurry specific gravity 1.49-1.51 g / cm 3 , glaze slurry flow rate 13 ~ 15s / 100mL, glaze slurry sieve residue 250 mesh sieve residue 0.5% ~ 0.7%, glaze amount 440 ~ 550g / m 2 ;
[0018] (5) performing pattern decoration printing on the base glaze decoration layer several times to obtain a pattern decoration layer;
[0019] (6) Spray glazing on the pattern decoration layer to obtain a surface glaze decoration layer. The process parameters of spray glazing are: glaze slurry specific gravity 1.15-1.25 g / cm 3 , glaze slurry flow rate 11 ~ 13s / 100mL, glaze slurry sieve residue 250 mesh sieve residue 0.5% ~ 0.7%, glaze amount 145 ~ 220g / m 2 ;
[0020] (7) Applying functional glaze on the surface glaze decorative layer to obtain a functional glaze decorative layer, the process parameters of which are: glaze slurry specific gravity 1.4-1.5 g / cm 3 , glaze slurry flow rate 55~60s / 100mL, glaze amount: 150~220g / m 2 ;
[0021] (8) The semi-finished product decorated in the above steps is fired at a temperature of 1180° C. to 1200° C. for 360 to 480 minutes to obtain the ceramic permeable brick with the imitation stone texture.
[0022] The ceramic waste bricks in the present invention refer to the ceramic waste products such as rock slabs, polished bricks, antique bricks, imitation stone bricks, daily ceramics, etc. produced by various ceramic enterprises, which were previously mainly used as building fillers or waste materials. The method for recycling and homogenizing ceramic waste bricks is: the ceramic waste bricks are distinguished according to whiteness and water absorption rate, and the waste bricks with different whiteness and water absorption rate are placed separately, and they are subjected to multiple rounds of turning and homogenization.
[0023] Preferably, the base material blank described in step (3) comprises the following components, by mass: 15 to 25 parts of 6-8 mesh variegated ceramic waste bricks, 45 to 55 parts of 8-14 mesh variegated ceramic waste bricks, 15 to 25 parts of 14-30 mesh variegated ceramic waste bricks, 8 to 12 parts of 30 mesh or less variegated ceramic waste bricks, 6 to 10 parts of binder and 3 to 5 parts of water.
[0024] It is further preferred that the base material blank described in step (3) comprises the following components, by mass: 20 parts of 6-8 mesh variegated ceramic waste bricks, 50 parts of 8-14 mesh variegated ceramic waste bricks, 20 parts of 14-30 mesh variegated ceramic waste bricks, 10 parts of 30 mesh or less variegated ceramic waste bricks, 8 parts of binder and 4 parts of water.
[0025] Preferably, the fabric blank described in step (2) comprises the following components, by mass: 8 to 12 parts of white ceramic waste bricks of 8 to 14 mesh, 30 to 40 parts of white ceramic waste bricks of 14 to 30 mesh, 18 to 22 parts of variegated ceramic waste bricks of 8 to 14 mesh, 20 to 30 parts of variegated ceramic waste bricks of 14 to 30 mesh, 8 to 12 parts of variegated ceramic waste bricks below 30 mesh, 6 to 10 parts of binder and 3 to 5 parts of water.
[0026] Further preferably, the fabric blank described in step (2) comprises the following components, by mass: 10 parts of white ceramic waste bricks of 8-14 mesh, 35 parts of white ceramic waste bricks of 14-30 mesh, 20 parts of variegated ceramic waste bricks of 8-14 mesh, 25 parts of variegated ceramic waste bricks of 14-30 mesh, 10 parts of variegated ceramic waste bricks below 30 mesh, 8 parts of binder and 4 parts of water.
[0027] The mixing steps of the surface blank or the base material blank are specifically as follows: the ceramic waste brick particles configured in proportion are sequentially put into the mixer and stirred for 2 minutes, water is added and stirred for 3 minutes to make the surface of the ceramic waste brick particles evenly wet, and then a binder is added and stirred for 4 minutes.
[0028] Preferably, the binder described in step (2) or (3) comprises the following components, measured in parts by mass: 80-88 parts of bentonite, 0.8-1.2 parts of methyl cellulose, 8-12 parts of kaolin and 4-6 parts of albite.
[0029] Further preferably, the binder described in step (2) or (3) comprises the following components, in parts by mass: 84 parts of bentonite, 1 part of methyl cellulose, 10 parts of kaolin and 5 parts of albite.
[0030] Preferably, the base glaze formula in the base glaze decorative layer described in step (4) is: calculated by dry weight, including 22-28 parts of potassium feldspar, 6-10 parts of zirconium silicate, 0.1-0.3 parts of methyl cellulose, 0.2-0.4 parts of sodium tripolyphosphate, 6-10 parts of barium carbonate, 6-10 parts of kaolin, 12-18 parts of albite, 8-12 parts of aluminum chloride, 3-5 parts of zinc oxide, 5-10 parts of quartz, 1-3 parts of calcined talc and 4-6 parts of nepheline, and an additional 45-55 parts of water.
[0031] Further preferably, the base glaze formula in the base glaze decorative layer described in step (4) is: calculated by dry weight, including 25 parts of potassium feldspar, 8 parts of zirconium silicate, 0.2 parts of methyl cellulose, 0.3 parts of sodium tripolyphosphate, 8 parts of barium carbonate, 8 parts of kaolin, 15 parts of albite, 10 parts of aluminum chloride, 4 parts of zinc oxide, 7 parts of quartz, 2 parts of talc and 5 parts of nepheline, and an additional 50 parts of water.
[0032] Preferably, the glaze formula in the glaze decorative layer described in step (6) is: calculated by dry weight, including 28-32 parts of potassium feldspar, 0.1-0.3 parts of methyl cellulose, 0.1-0.3 parts of sodium tripolyphosphate, 15-20 parts of barium carbonate, 8-10 parts of dolomite, 13-18 parts of sodium feldspar, 6-10 parts of calcined talc, 3-5 parts of zinc oxide, 5-10 parts of kaolin and 5-10 parts of low-temperature frit, and an additional 45-55 parts of water.
[0033] Further preferably, the glaze formula in the glaze decorative layer described in step (6) is: calculated by dry weight, including 30 parts of potassium feldspar, 0.2 parts of methyl cellulose, 0.2 parts of sodium tripolyphosphate, 18 parts of barium carbonate, 9 parts of dolomite, 15 parts of sodium feldspar, 8 parts of calcined talc, 4 parts of zinc oxide, 8 parts of kaolin and 8 parts of low-temperature frit, and an additional 50 parts of water.
[0034] Preferably, the functional glaze formula in the functional glaze decorative layer of step (7) is: calculated by weight, including 66-68 parts of dry particle suspension agent, 0.1-0.3 parts of methyl cellulose, 10-20 parts of water and 18-22 parts of environmentally friendly dry particles.
[0035] Further preferably, the functional glaze formula in the functional glaze decorative layer described in step (7) is: calculated by weight, including 66 parts of dry particle suspension agent, 0.1 parts of methyl cellulose, 16 parts of water and 18 parts of environmentally friendly dry particles.
[0036] Compared with the prior art, the present invention has the following advantages: Compared with the existing ceramic permeable bricks on the market, the present invention has the following advantages on the premise of having the permeable function: 1. The product texture is clear and the pattern effect is rich; 2. The product color is optional, and the color and texture of the existing stone can be reproduced, which is unattainable by the existing permeable bricks on the market; 3. The surface glaze decoration is added, and the anti-fouling performance is significantly improved compared with the existing permeable bricks on the market (as shown below Figure 3 4. Add functional glaze, the anti-slip performance can reach 60BPN. Description of the drawings:
[0037] Figure 1 It is a structural schematic diagram of the ceramic permeable brick proposed by the present invention;
[0038] Figure 2 is a surface image of the base glaze decoration layer obtained after base glaze decoration in Example 1;
[0039] Figure 3 1 is a comparison chart of the antifouling ability of the ceramic permeable brick obtained in Example 1 and the existing ceramic permeable bricks on the market, wherein 1 and 2 are the comparisons before and after the antifouling of Example 1; 3 and 4 are the comparisons before and after the antifouling of the existing ceramic permeable bricks on the market;
[0040] Description of the drawings: 1. Green body base material layer; 2. Green body surface material layer; 3. Base glaze decoration layer; 4. Pattern decoration layer; 5. Top glaze decoration layer; 6. Functional glaze decoration layer. Specific implementation method:
[0041] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.
[0042] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the experimental materials and reagents in this article are conventional commercial products in the field of this technology. Low-temperature frits were purchased from Tangye frit factory with the item number C0018; dry granular suspension was purchased from Ke Minghai with the item number C0067; methyl cellulose was purchased from Cui Xin with the item number CVH9; environmentally friendly dry granules (ceramic dry granules) were purchased from Foshan Zhongrunlin Building Materials Technology Co., Ltd.
[0043] like Figure 1 As shown, a ceramic permeable brick with imitation stone texture includes, from bottom to top, a body base material layer 1, a body surface layer 2, a base glaze decoration layer 3, a pattern decoration layer 4, a surface glaze decoration layer 5 and a functional glaze decoration layer 6.
[0044] The manufacturing method of the above-mentioned ceramic permeable brick with imitation stone texture has the following main process technology routes:
[0045] Waste ceramic brick recycling → crushing → body batching → mixing → spreading → pressing and molding → drying → base glaze decoration → glaze line drying → pattern digital decoration → surface glaze decoration → functional glaze decoration → firing.
[0046] The manufacturing method specifically comprises the following steps:
[0047] (1) Recycling and homogenization of waste ceramic bricks: Waste ceramic bricks refer to the waste ceramic products such as rock slabs, polished bricks, antique bricks, imitation stone bricks, and daily-use ceramics produced by various ceramic enterprises. They were previously mainly used as building fillers or waste materials. The recycling and homogenization methods are as follows: waste bricks are classified according to whiteness and water absorption rate, waste bricks of different whiteness and water absorption rate are placed separately, and they are subjected to multiple rounds of turning and homogenization;
[0048] (2) Crush the waste ceramic bricks to obtain crushed materials, which are crushed separately by jaw crushers and hammer crushers, and the crushed materials are classified by particle size after high magnetic iron removal, mainly into: 6-8 mesh, 8-14 mesh, 14-30 mesh and above 30 mesh, so as to facilitate the adjustment of the formula of product size, bending resistance, water permeability and other physical properties;
[0049] (3) The crushed ceramic waste brick particles classified in step (2) are respectively prepared into surface material and base material according to whiteness and particle size, and the base material is mixed with a binder, and the moisture content of the mixed ingredients is controlled to be 3.8% to 4.2%. The mixture is held in a sticky mass by hand, and the base material blank is obtained after being mixed evenly. The base material blank is pressed into shape and dried to obtain a blank base material layer 1;
[0050] (4) mixing the fabric obtained in step (3) with a binder, controlling the moisture content of the mixed ingredients to be 3.8% to 4.2%, and mixing them evenly to obtain a fabric blank, pressing the fabric blank into a shape, and drying it to obtain a blank fabric layer 2;
[0051] (5) Applying a base glaze on the body surface layer to obtain a base glaze decorative layer 3. The process parameters for applying the base glaze are: glaze slurry specific gravity 1.49-1.51 g / cm 3 , glaze slurry flow rate 13 ~ 15s / 100mL, glaze slurry sieve residue 250 mesh sieve residue 0.5% ~ 0.7%, glaze amount 440 ~ 550g / m 2 ;
[0052] (6) Printing pattern decorations on the base glaze decoration layer several times to obtain a pattern decoration layer 4;
[0053] (7) Spray glazing on the pattern decoration layer to obtain the surface glaze decoration layer 5. The process parameters of spray glazing are: glaze slurry specific gravity 1.15-1.25 g / cm 3 , glaze slurry flow rate 11 ~ 13s / 100mL, glaze slurry sieve residue 250 mesh sieve residue 0.5% ~ 0.7%, glaze amount 145 ~ 220g / m 2 ;
[0054] (8) Applying functional glaze on the surface glaze decorative layer to obtain the functional glaze decorative layer 6, the process parameters of which are: glaze slurry specific gravity 1.4-1.5 g / cm 3 , glaze slurry flow rate 55 ~ 60s / 100mL, glaze amount: 150 ~ 220g / m 2 ;
[0055] (9) The semi-finished product decorated in the above steps is fired at a temperature of 1180° C. to 1200° C. for 360 to 480 minutes to obtain a ceramic permeable brick with a stone-like texture, which meets the GB / T25993-2023 permeable pavement brick and permeable road panel standard.
[0056] The following preferred embodiment is that the mixing step of the surface material blank or the base material blank in step (3) or (4) is specifically as follows: the ceramic waste brick particles configured in proportion are sequentially fed into the mixer and stirred for 2 minutes, water is added and stirred for 3 minutes to make the surface of the ceramic waste brick particles evenly moistened, and then a binder is added and stirred for 4 minutes.
[0057] The following preferred embodiment, the specific steps of pressing and forming in step (3) or (4) are: the uniformly mixed blank is sent to the hopper on the top of the press via a conveyor belt, and is pressed using a Henglitai 1501 type permeable brick special press, and the pressure is set according to the green strength and permeability.
[0058] The following preferred embodiments are as follows: the specific steps of drying in step (3) or (4) are as follows: the pressed body is conveyed to a roller kiln for drying, the drying temperature is set to 100°C, the drying time is 10 minutes, and the temperature of the body after drying is controlled at 40°C to 45°C to provide a drying temperature for the subsequent base glaze. The drying temperature has a great influence on the color and texture of the fired product.
[0059] In the following preferred embodiments, the base material blank of step (3) comprises the following components by mass: 15-25 parts of 6-8 mesh variegated ceramic waste bricks, 45-55 parts of 8-14 mesh variegated ceramic waste bricks, 15-25 parts of 14-30 mesh variegated ceramic waste bricks, 8-12 parts of 30 mesh variegated ceramic waste bricks, 6-10 parts of binder and 3-5 parts of water. Further preferably, the base material blank comprises the following components by mass: 20 parts of 6-8 mesh variegated ceramic waste bricks, 50 parts of 8-14 mesh variegated ceramic waste bricks, 20 parts of 14-30 mesh variegated ceramic waste bricks, 10 parts of 30 mesh variegated ceramic waste bricks, 8 parts of binder and 4 parts of water.
[0060] In the following preferred embodiment, the fabric blank of step (3) comprises the following components by weight: 8-12 parts of 8-14 mesh white ceramic waste bricks, 30-40 parts of 14-30 mesh white ceramic waste bricks, 18-22 parts of 8-14 mesh variegated ceramic waste bricks, 20-30 parts of 14-30 mesh variegated ceramic waste bricks, 8-12 parts of 30 mesh variegated ceramic waste bricks, 6-10 parts of binder and 3-5 parts of water. Further preferably, the fabric blank comprises the following components by weight: 10 parts of 8-14 mesh white ceramic waste bricks, 35 parts of 14-30 mesh white ceramic waste bricks, 20 parts of 8-14 mesh variegated ceramic waste bricks, 25 parts of 14-30 mesh variegated ceramic waste bricks, 10 parts of 30 mesh variegated ceramic waste bricks, 8 parts of binder and 4 parts of water.
[0061] In the following preferred embodiments, the binder in step (3) or (4) comprises the following components by weight: 80-88 parts of bentonite, 0.8-1.2 parts of methyl cellulose, 8-12 parts of kaolin and 4-6 parts of albite. Further preferably, the binder comprises the following components by weight: 84 parts of bentonite, 1 part of methyl cellulose, 10 parts of kaolin and 5 parts of albite.
[0062] The following preferred embodiment, the base glaze formula in the base glaze decorative layer of step (5) is: based on dry weight, including 22-28 parts of potassium feldspar, 6-10 parts of zirconium silicate, 0.1-0.3 parts of methyl cellulose, 0.2-0.4 parts of sodium tripolyphosphate, 6-10 parts of barium carbonate, 6-10 parts of kaolin, 12-18 parts of albite, 8-12 parts of aluminum chloride, 3-5 parts of zinc oxide, 5-10 parts of quartz, 1-3 parts of calcined talc and 4-6 parts of nepheline, and 45-55 parts of water are added. The glazing effect is a dot distribution, and the glazing parameters and dotting effect need to be strictly controlled. This process point has a great influence on the water permeability and product color. Therefore, the glaze cabinet and glaze line are controlled by a frequency converter. By adjusting the frequency converter parameters, the glazing parameter requirements and effects are achieved. Further preferably, the base glaze formula in the base glaze decorative layer is: calculated by dry weight, including 25 parts of potassium feldspar, 8 parts of zirconium silicate, 0.2 parts of methyl cellulose, 0.3 parts of sodium tripolyphosphate, 8 parts of barium carbonate, 8 parts of kaolin, 15 parts of albite, 10 parts of aluminum chloride, 4 parts of zinc oxide, 7 parts of quartz, 2 parts of talc and 5 parts of nepheline, and 50 parts of water are added.
[0063] The following preferred embodiment, the specific steps of step (6) pattern decoration are: using a large-volume digital inkjet machine to print the pattern decoration several times on the blank of the base glaze decoration layer, the nozzle model is Xaar 2001.
[0064] In the following preferred embodiments, the glaze formula in the glaze decorative layer of step (7) is: by dry weight, including 28-32 parts of potassium feldspar, 0.1-0.3 parts of methyl cellulose, 0.1-0.3 parts of sodium tripolyphosphate, 15-20 parts of barium carbonate, 8-10 parts of dolomite, 13-18 parts of albite, 6-10 parts of calcined talc, 3-5 parts of zinc oxide, 5-10 parts of kaolin and 5-10 parts of low-temperature frit, and 45-55 parts of water are added. Further preferably, the glaze formula in the glaze decorative layer is: by dry weight, including 30 parts of potassium feldspar, 0.2 parts of methyl cellulose, 0.2 parts of sodium tripolyphosphate, 18 parts of barium carbonate, 9 parts of dolomite, 15 parts of albite, 8 parts of calcined talc, 4 parts of zinc oxide, 8 parts of kaolin and 8 parts of low-temperature frit, and 50 parts of water are added. The glazing effect of the surface glaze decorative layer is fan-shaped full coverage, and the glazing parameters need to be strictly controlled, which has a great impact on the color of the product.
[0065] In the following preferred embodiments, the functional glaze formula in the functional glaze decorative layer of step (8) is: by weight, including 66-68 parts of dry particle suspension agent, 0.1-0.3 parts of methyl cellulose, 10-20 parts of water and 18-22 parts of environmentally friendly dry particles. Further preferred, the functional glaze formula in the functional glaze decorative layer is: by weight, including 66 parts of suspension agent, 0.1 parts of methyl cellulose, 16 parts of water and 18 parts of environmentally friendly dry particles. In order to make the permeable bricks with stone texture meet certain performance requirements, the present invention adopts a glaze cabinet to spray the functional glaze water, and the glazing effect is a point distribution.
[0066] The following preferred embodiment has the specific conditions of firing in step (9): the semi-finished product decorated in the above steps is sent into a firing kiln for firing, the maximum firing temperature is 1180°C to 1200°C, the firing time is 360 to 480 minutes, wherein the firing time in the highest temperature stage is 60 minutes, the kiln length is 168 meters, and the internal width of the kiln is 2.1 meters.
[0067] The ceramic permeable bricks with imitation stone texture are tested for product size, flatness accuracy and internal quality performance (the main test indicators are shown in Table 1-3), which conforms to the GB / T25993-2023 permeable pavement brick and permeable road panel standard. Wear resistance: the length of the wear pit should not be greater than 35mm, anti-slip: the anti-slip BPN value should not be less than 60.
[0068] Table 1 Dimensions (mm)
[0069]
[0070] Table 2 Flexural strength (MPa)
[0071] Flexural strength grade average value Single block minimum 3.0 ≥3.0 ≥2.4 3.5 ≥3.5 ≥2.8 4.0 ≥4.0 ≥3.2 4.5 ≥4.5 ≥3.6 5.5 ≥5.5 ≥4.4 6.5 ≥6.5 ≥5.2
[0072] Table 3 Water permeability coefficient (cm / sec)
[0073] Permeability level Permeability Class B ≥1.0×10-2
[0074] Example 1
[0075] A method for manufacturing a ceramic permeable brick with imitation stone texture, specifically comprising the following steps:
[0076] (1) Recycling and homogenization of ceramic waste bricks: Ceramic waste bricks are classified according to whiteness and water absorption rate, and waste bricks of different whiteness and water absorption rate are placed separately, and they are subjected to multiple rounds of turning and homogenization;
[0077] (2) Crush the waste ceramic bricks to obtain crushed materials, which are crushed separately by jaw crushers and hammer crushers, and the crushed materials are classified by particle size after high magnetic iron removal, mainly into: 6-8 mesh, 8-14 mesh, 14-30 mesh and below 30 mesh, so as to facilitate the adjustment of the formula of product size, bending resistance, water permeability and other physical properties;
[0078] (3) The ceramic waste brick particles and crushed materials classified in step (2) are respectively prepared into surface materials and base materials according to whiteness and particle size, and the base material is mixed with a binder. The moisture content of the mixed ingredients is controlled at 3.8% to 4.2%, and the mixture is held in a sticky mass by hand. After uniform mixing, a base material blank is obtained. The base material blank comprises the following components by weight: 20 parts of 6-8 mesh variegated ceramic waste bricks, 50 parts of 8-14 mesh variegated ceramic waste bricks, 20 parts of 14-30 mesh variegated ceramic waste bricks, 10 parts of 30 mesh variegated ceramic waste bricks, 8 parts of a binder and 4 parts of water. The binder comprises the following components by weight: 84 parts of bentonite, 1 part of methyl cellulose, 10 parts of kaolin and 5 parts of albite. The base material blank is pressed into shape and dried to obtain a base material layer 1 of a blank.
[0079] (4) Mixing the fabric obtained in step (3) with a binder, controlling the moisture content of the mixed ingredients to be 3.8% to 4.2%, and mixing them evenly to obtain a fabric blank, which comprises the following components by mass: 10 parts of white ceramic waste bricks with a mesh size of 8 to 14, 35 parts of white ceramic waste bricks with a mesh size of 14 to 30, 20 parts of variegated ceramic waste bricks with a mesh size of 8 to 14, 25 parts of variegated ceramic waste bricks with a mesh size of 14 to 30, 10 parts of variegated ceramic waste bricks with a mesh size of less than 30, 8 parts of a binder, and 4 parts of water. The binder comprises the following components by mass: 84 parts of bentonite, 1 part of methyl cellulose, 10 parts of kaolin, and 5 parts of albite. Pressing the fabric blank into a shape and drying it to obtain a blank fabric layer 2;
[0080] (5) Applying a base glaze on the body surface layer to obtain a base glaze decorative layer 3 (such as Figure 2 The process parameters of pouring bottom glaze are as follows: glaze slurry specific gravity 1.49~1.51g / cm 3, glaze slurry flow rate 13 ~ 15s / 100mL, glaze slurry sieve residue 250 mesh sieve residue 0.5% ~ 0.7%, glaze amount 440 ~ 550g / m 2 The base glaze formula is: based on dry weight, it includes 25 parts of potassium feldspar, 8 parts of zirconium silicate, 0.2 parts of methyl cellulose, 0.3 parts of sodium tripolyphosphate, 8 parts of barium carbonate, 8 parts of kaolin, 15 parts of sodium feldspar, 10 parts of aluminum chloride, 4 parts of zinc oxide, 7 parts of quartz, 2 parts of calcined talc, 5 parts of nepheline and 50 parts of water;
[0081] (6) Printing the pattern decoration on the base glaze decoration layer five times using a large-volume digital inkjet printer, the inkjet printer ink installation sequence is: blue - golden brown - yellow - black - wrapped red, the nozzle model is Xaar 2001, and the pattern decoration layer 4 is obtained;
[0082] (7) Spray glazing on the pattern decoration layer to obtain the surface glaze decoration layer 5. The process parameters of spray glazing are: glaze slurry specific gravity 1.15-1.25 g / cm 3 , glaze slurry flow rate 11 ~ 13s / 100mL, glaze slurry sieve residue 250 mesh sieve residue 0.5% ~ 0.7%, glaze amount 145 ~ 220g / m 2 The glaze formula is: based on dry weight, it includes 30 parts of potassium feldspar, 0.2 parts of methyl cellulose, 0.2 parts of sodium tripolyphosphate, 18 parts of barium carbonate, 9 parts of dolomite, 15 parts of sodium feldspar, 8 parts of calcined talc, 4 parts of zinc oxide, 8 parts of kaolin and 8 parts of low-temperature frit, and 50 parts of water are added;
[0083] (8) Applying functional glaze on the surface glaze decorative layer to obtain the functional glaze decorative layer 6, the process parameters of which are: glaze slurry specific gravity 1.4-1.5 g / cm 3 , glaze slurry flow rate 55 ~ 60s / 100mL, glaze amount: 150 ~ 220g / m 2 The formula of the functional glaze is: by mass, it includes 66 parts of dry particle suspension agent, 0.1 parts of methylcellulose, 16 parts of water and 18 parts of environmentally friendly dry particles;
[0084] (9) The semi-finished product decorated in the above steps is fired, with the highest firing temperature being 1180° C. to 1200° C. and the firing time being 360 to 480 minutes, wherein the firing time in the highest temperature stage is 60 minutes, to obtain a ceramic permeable brick with a stone-like texture.
[0085] The ceramic permeable brick has a base material layer thickness of about 50 mm, a surface material layer thickness of about 9 mm, a base glaze decorative layer thickness of about 0.15 mm, a surface glaze decorative layer thickness of about 0.05 mm, and a functional glaze decorative layer thickness of about 0.6 mm.
[0086] Comparative Example 1
[0087] The method is the same as Example 1, except that in step (5), the equipment and process used in conventional bell jar glazing and water jet glazing are used.
[0088] Compared with Comparative Example 1, the bottom glaze in Example 1 is sprayed with a glaze throwing machine (such as Figure 2 ), while ensuring that the pattern decoration layer is closer to the color and texture of natural stone, and at the same time ensuring that the water permeability coefficient is ≥1.0×10 -2 .
[0089] Comparative Example 2
[0090] The method is the same as Example 1, except that step (8) is omitted, and the thickness of the surface glaze decorative layer is the sum of the thicknesses of the surface glaze decorative layer and the functional glaze decorative layer in Example 1.
[0091] The anti-slip performance of Example 1 and Comparative Example 2 is compared, as shown in Table 2:
[0092] Table 2
[0093] No functional glaze decorative layer (Comparative Example 2) With functional glaze decorative layer (Example 1) BPN>50 BPN>60
[0094] Example 2
[0095] Same as Example 1, except that:
[0096] The base material of step (3) comprises the following components by weight: 15 parts of 6-8 mesh variegated ceramic waste bricks, 55 parts of 8-14 mesh variegated ceramic waste bricks, 15 parts of 14-30 mesh variegated ceramic waste bricks, 12 parts of 30 mesh variegated ceramic waste bricks, 6 parts of binder and 5 parts of water. The surface material comprises the following components by weight: 8 parts of 8-14 mesh white ceramic waste bricks, 40 parts of 14-30 mesh white ceramic waste bricks, 18 parts of 8-14 mesh variegated ceramic waste bricks, 30 parts of 14-30 mesh variegated ceramic waste bricks, 8 parts of 30 mesh variegated ceramic waste bricks, 10 parts of binder and 3 parts of water. The binder in step (3) or (4) comprises the following components by weight: 80 parts of bentonite, 0.8 parts of methyl cellulose, 8 parts of kaolin and 4 parts of albite.
[0097] The base glaze formula in the base glaze decorative layer of step (5) is: calculated by dry weight, including 22 parts of potassium feldspar, 6 parts of zirconium silicate, 0.1 parts of methyl, 0.2 parts of trimer, 6 parts of barium carbonate, 6 parts of kaolin, 12 parts of albite, 8 parts of aluminum chloride, 3 parts of zinc oxide, 5 parts of quartz, 1 part of talc and 4 parts of nepheline, and an additional 45 parts of water.
[0098] The glaze formula in the glaze decorative layer of step (7) is: calculated by dry weight, including 32 parts of potassium feldspar, 0.3 parts of methyl, 0.3 parts of trimer, 20 parts of barium carbonate, 10 parts of dolomite, 18 parts of albite, 10 parts of calcined talc, 5 parts of zinc oxide, 10 parts of kaolin and 10 parts of low-temperature frit, and an additional 55 parts of water.
[0099] The functional glaze formula in the functional glaze decorative layer of step (8) is: calculated by weight, including 66 parts of dry particle suspension agent, 0.1 parts of methyl cellulose, 16 parts of water and 18 parts of environmentally friendly dry particles.
[0100] Example 3
[0101] Same as Example 1, except that:
[0102] The base material of step (3) comprises the following components by weight: 25 parts of 6-8 mesh variegated ceramic waste bricks, 45 parts of 8-14 mesh variegated ceramic waste bricks, 25 parts of 14-30 mesh variegated ceramic waste bricks, 8 parts of 30 mesh variegated ceramic waste bricks, 10 parts of binder and 3 parts of water. The surface material comprises the following components by weight: 12 parts of 8-14 mesh white ceramic waste bricks, 30 parts of 14-30 mesh white ceramic waste bricks, 22 parts of 8-14 mesh variegated ceramic waste bricks, 20 parts of 14-30 mesh variegated ceramic waste bricks, 12 parts of 30 mesh variegated ceramic waste bricks, 6 parts of binder and 5 parts of water. The binder in step (3) or (4) comprises the following components by weight: 88 parts of bentonite, 1.2 parts of methyl, 12 parts of kaolin and 6 parts of albite.
[0103] The base glaze formula in the base glaze decorative layer of step (5) is as follows: in parts by mass, it includes 28 parts of potassium feldspar, 10 parts of zirconium silicate, 0.3 parts of methyl, 0.4 parts of trimer, 10 parts of barium carbonate, 10 parts of kaolin, 18 parts of albite, 12 parts of aluminum chloride, 5 parts of zinc oxide, 10 parts of quartz, 3 parts of talc and 6 parts of nepheline, and an additional 55 parts of water.
[0104] The glaze formula in the glaze decorative layer of step (7) is as follows: in parts by mass, it includes 28 parts of potassium feldspar, 0.1 parts of methyl cellulose, 0.1 parts of sodium tripolyphosphate, 15 parts of barium carbonate, 8 parts of dolomite, 13 parts of sodium feldspar, 6 parts of calcined talc, 3 parts of zinc oxide, 5 parts of kaolin and 5 parts of low-temperature frit, and an additional 45 parts of water.
[0105] The functional glaze formula in the functional glaze decorative layer of step (8) is: calculated by weight, including 68 parts of dry particle suspension agent, 0.1 parts of methyl cellulose, 10 parts of water and 22 parts of environmentally friendly dry particles.
[0106] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A ceramic permeable brick with imitation stone texture, characterized in that: The ceramic permeable bricks include a base material layer, a base material layer, a base glaze decoration layer, a pattern decoration layer, a surface glaze decoration layer and a functional glaze decoration layer from bottom to top. The ratio of the nominal length to the nominal thickness of the ceramic permeable bricks is less than or equal to 4. When the ceramic permeable bricks are permeable pavement bricks, the splitting tensile strength is ≥3.0 MPa, and the water permeability coefficient is greater than or equal to 1.0×10 -2 cm / s; the ratio of the nominal length to the nominal thickness of the ceramic permeable brick is greater than 4. When it is a permeable road panel, the flexural strength is ≥3.0 MPa, and the permeability coefficient is greater than or equal to 1.0×10 -2 cm / s.
2. The ceramic permeable brick with imitation stone texture according to claim 1, characterized in that: The surface glaze decoration layer is prepared by the following steps: spray glazing is performed on the pattern decoration layer to obtain the surface glaze decoration layer, and the process parameters of the spray glazing are: the specific gravity of the glaze slurry is 1.15-1.25g / cm 3 , glaze slurry flow rate 11 ~ 13s / 100mL, glaze slurry sieve residue 250 mesh sieve residue 0.5% ~ 0.7%, glaze amount 145 ~ 220g / m 2 .
3. The ceramic permeable brick with imitation stone texture according to claim 1 or 2, characterized in that: The glaze formula in the glaze decorative layer is: calculated by dry weight, including 28-32 parts of potassium feldspar, 0.1-0.3 parts of methyl cellulose, 0.1-0.3 parts of sodium tripolyphosphate, 15-20 parts of barium carbonate, 8-10 parts of dolomite, 13-18 parts of sodium feldspar, 6-10 parts of calcined talc, 3-5 parts of zinc oxide, 5-10 parts of kaolin and 5-10 parts of low-temperature frit, and an additional 45-55 parts of water.
4. The ceramic permeable brick with imitation stone texture according to claim 1, characterized in that: The functional glaze formula in the functional glaze decorative layer is as follows: by weight, it includes 62-70 parts of dry particle suspension agent, 0.1-0.3 parts of methyl cellulose, 13-20 parts of water and 15-18 parts of environmentally friendly dry particles.
5. The method for manufacturing the ceramic permeable brick with imitation stone texture according to claim 1, characterized in that: The steps include: (1) Crush the waste ceramic bricks to obtain crushed materials, remove iron from the crushed materials and classify them according to their particle sizes, namely: 6-8 mesh, 8-14 mesh, 14-30 mesh and below 30 mesh; (2) The crushed ceramic waste brick particles classified in step (1) are respectively prepared into a surface material and a base material according to whiteness and particle size, the base material is mixed with a binder, the moisture content of the mixed ingredients is controlled at 3.8% to 4.2%, and the base material blank is obtained after being evenly mixed, and the base material blank is pressed into a blank base material layer; (3) mixing the fabric obtained in step (2) with a binder, controlling the moisture content of the mixed ingredients to be 3.8% to 4.2%, mixing evenly to obtain a fabric blank, and pressing the fabric blank into a blank fabric layer; (4) Applying a base glaze on the surface layer of the blank to obtain a base glaze decorative layer. The process parameters for applying the base glaze are: glaze slurry specific gravity 1.49-1.51 g / cm 3 , glaze slurry flow rate 13 ~ 15s / 100mL, glaze slurry sieve residue 250 mesh sieve residue 0.5% ~ 0.7%, glaze amount 440 ~ 550g / m 2 ; (5) performing pattern decoration printing on the base glaze decoration layer several times to obtain a pattern decoration layer; (6) Spray glazing on the pattern decoration layer to obtain a surface glaze decoration layer. The process parameters of spray glazing are: glaze slurry specific gravity 1.15-1.25 g / cm 3 , glaze slurry flow rate 11 ~ 13s / 100mL, glaze slurry sieve residue 250 mesh sieve residue 0.5% ~ 0.7%, glaze amount 145 ~ 220g / m 2 ; (7) Applying functional glaze on the surface glaze decorative layer to obtain a functional glaze decorative layer, the process parameters of which are: glaze slurry specific gravity 1.4-1.5 g / cm 3 , glaze slurry flow rate 55 ~ 60s / 100mL, glaze amount: 150 ~ 220g / m 2 ; (8) The semi-finished product decorated in the above steps is fired at a temperature of 1180° C. to 1200° C. for 360 to 480 minutes to obtain the ceramic permeable brick with the imitation stone texture.
6. The manufacturing method according to claim 5, characterized in that: The base material blank described in step (2) comprises the following components, by weight: 15 to 25 parts of 6-8 mesh variegated ceramic waste bricks, 45 to 55 parts of 8-14 mesh variegated ceramic waste bricks, 15 to 25 parts of 14-30 mesh variegated ceramic waste bricks, 8 to 12 parts of 30 mesh variegated ceramic waste bricks, 6 to 10 parts of binder and 3 to 5 parts of water; the surface material blank described in step (3) comprises the following components, by weight: 8 to 12 parts of 8-14 mesh white ceramic waste bricks, 30 to 40 parts of 14-30 mesh white ceramic waste bricks, 18 to 22 parts of 8-14 mesh variegated ceramic waste bricks, 20 to 30 parts of 14-30 mesh variegated ceramic waste bricks, 8 to 12 parts of 30 mesh variegated ceramic waste bricks, 6 to 10 parts of binder and 3 to 5 parts of water.
7. The manufacturing method according to claim 5 or 6, characterized in that: The binder described in step (2) or (3) comprises the following components, calculated by weight: 80 to 88 parts of bentonite, 0.8 to 1.2 parts of methyl cellulose, 8 to 12 parts of kaolin and 4 to 6 parts of albite.
8. The manufacturing method according to claim 5, characterized in that: The base glaze formula in the base glaze decorative layer described in step (4) is: calculated by dry weight, including 22-28 parts of potassium feldspar, 6-10 parts of zirconium silicate, 0.1-0.3 parts of methyl cellulose, 0.2-0.4 parts of sodium tripolyphosphate, 6-10 parts of barium carbonate, 6-10 parts of kaolin, 12-18 parts of albite, 8-12 parts of aluminum chloride, 3-5 parts of zinc oxide, 5-10 parts of quartz, 1-3 parts of calcined talc and 4-6 parts of nepheline, and an additional 45-55 parts of water.
9. The manufacturing method according to claim 5, characterized in that: The glaze formula in the glaze decorative layer described in step (6) is: calculated by dry weight, including 28-32 parts of potassium feldspar, 0.1-0.3 parts of methyl cellulose, 0.1-0.3 parts of sodium tripolyphosphate, 15-20 parts of barium carbonate, 8-10 parts of dolomite, 13-18 parts of albite, 6-10 parts of calcined talc, 3-5 parts of zinc oxide, 5-10 parts of kaolin and 5-10 parts of low-temperature frit, and an additional 45-55 parts of water.
10. The manufacturing method according to claim 5, characterized in that: The functional glaze formula in the functional glaze decorative layer described in step (7) is: calculated by weight, including 66-68 parts of dry particle suspension agent, 0.1-0.3 parts of methyl cellulose, 10-20 parts of water and 18-22 parts of environmentally friendly dry particles.
Citation Information
Patent Citations
Dry-granular glazed ceramic tile and preparation method thereof
CN109354413A
Imitation marble ceramic water permeable brick and preparation method thereof
CN109534786A
Glass waste residue ceramic water permeable brick and preparation process thereof
CN110981422A
Fine matte dry granular glaze ceramic tile and preparation method thereof
CN116199529A
Method for preparing glazed permeable brick by utilizing various inferior raw materials
CN116217205A
Cited By
Ceramic water permeable brick with surface coating and preparation process of ceramic water permeable brick
CN120535286A